Operational Standard for Point-through-point Electroacupuncture Therapy of Traditional Chinese Medicine Rehabilitation Techniques - Working Group on Operational Standard for Point-through-point Electroacupuncture Therapy of Traditional Chinese Medicine Rehabilitation Techniques (康复学报)
Point-through-point electroacupuncture therapy is a kind of acupuncture therapy method piercing through the point with the millimeter-needle. With this method, one needle acts on a certain part of the human body through multiple acupoints, and when needling bring about the desired sensation, the pulse current is output by an electroacupuncture apparatus, so as to prevent and treat diseases. Compared with conventional acupuncture, point-through-point electroacupuncture therapy has a wider scope of action and stronger acupuncture stimulation, resulting in the effects of dispersing meridians and clearing collaterals, promoting blood circulation and relieving pain and so on. It has been widely used in the treatment of various clinical diseases. The main purpose of establishing the operational standard for point-through-point electroacupuncture therapy of traditional Chinese medicine rehabilitation techniques is to standardize management and guide professionals and technical personnel of traditional Chinese medicine to correctly use point-through-point electroacupuncture therapy for rehabilitation. This standard includes the technical scope of point-through-point electroacupuncture therapy, normative references, terminology and definitions, operating procedures and requirements, main indications, contraindications, precautions and other aspects, and focuses on the pre-operative preparations (preparation of electroacupuncture apparatus, needling tools, acupoint selection, body position, hygienic environment requirements, aseptic techniques), the operation process (point-through-point method, determination of the desired sensation, connecting electroacupuncture), and post-operative procedures and requirements. This operational standard could be applied to guide the professionals and technical personnel of traditional Chinese medicine in hospitals at all levels and medical and health care institutions to carry out point-through-point electroacupuncture therapy for rehabilitation, with wide generality and effectiveness.